![\begin{gathered} a)2x+h-4 \\ b)\lim _(h\to0)2x-4 \\ c)x=-1,f^(\prime)(1)=-2 \\ x=2,f^(\prime)(2)=0 \\ x=3,f^(\prime)(3)=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/4jeti4siqir6ov8jlxqdyqeyc10u4w5ec4.png)
1) Considering that quadratic equation, we can find and simplify this expression that presents the limit of this function as h approaches 0.
a)
![\begin{gathered} (f(x+h)-f(x))/(h)= \\ ((x+h)^2-4(x+h)+1-(x^2-4x+1))/(h) \\ (x^2+2xh+h^2-4x+4h+1-x^2+4x-1)/(h) \\ (2xh+h^2-4h)/(h) \\ (h\left(2x+h-4\right))/(h) \\ 2x+h-4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/t4lh5j021vcdhlg6whwmsrejc1qfxuf55l.png)
b) When h becomes very close to zero, we can find this:
![\begin{gathered} 2x+0-4 \\ 2x-4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1ovsxdpzn68ir93vg1igwy1i37fiodq0o3.png)
In other words, we find the limit of this function (or the first derivative) as h approaches 0.
c) Let's use this simplified expression to find the instantaneous rate of change at x=1,x=2, and x=3
![\begin{gathered} f^(\prime)(x)=\lim _(h\to0)2x-4 \\ f^(\prime)(1)=\lim _(h\to0)2x-4=2(1)-4=-2 \\ f^(\prime)(2)=\lim _(h\to0)2x-4=2(2)-4=0 \\ f^(\prime)(3)=\lim _(h\to0)2x-4=2(3)-4=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qyymq9ey59wnu1xyp4y32h8djh7pxmuutx.png)